Novel two dimensional B2C3 monolayer as a high theoretical capacity anode material for Li or Na ion batteries - Xi Zhu; Keyang Wu; Beibei Ma; Xiao Wang; Detong Kong; Yuan Wang (Scientific Reports)
Abstract In this study, we utilized first-principles calculations to design a novel class of two-dimensional (2D) polycyclic materials composed of carbon and boron atoms, termed k-B2C3, which hold significant promise as high-capacity, fast-diffusing anode materials for Li/Na-ion batteries. We investigated the thermodynamic stability, mechanical properties, electronic structure, and energy storage characteristics of k-B2C3. The results reveal that k-B2C3 exhibits a density of states at the Fermi level of 0.18 states/eV, a Young’s modulus of $$274.43\text{ GPa}· \text{mm}$$ , and a Poisson’s ratio of 0.43, indicating excellent metallic conductivity and mechanical ductility, which are crucial for stability during charge/discharge cycles. Furthermore, the Li/Na diffusion barriers for k-B2C3 are 0.55 eV and 0.17 eV, respectively, which are vital for efficient charge/discharge processes. Most notably, k-B2C3 demonstrates a high theoretical storage capacity of 930 mAhg−1 for both Li and Na, coupled with low open-circuit voltages (1.30–0.54 V for Li and 1.17–0.34 V for Na). These findings suggest that 2D k-B2C3 is a promising candidate for use as an anode material in Li/Na-ion batteries and provides valuable insights for the development of advanced 2D electrode materials.